Investigation of bubble–particle attachment interaction during flotation - Zhou, Y.; Albijanic, Boris; Tadesse, Bogale; Wang, Y.; Yang, J. (Elsevier, 2019)
The controlling step for successful flotation is a bubble–particle attachment mechanism. Induction times cannot be measured directly in flotation cells due to the presence of a large number of bubbles and particles. Thus, the possibility is to determine induction times using fundamental flotation models. The focus of this technical note is to determine the induction times in a flotation column under different chemical environments and thus evaluate whether the induction times can be used to predict the flotation recoveries. In this work, the sized pyrite particles (−212 + 150 μm, −150 + 75 μm and −75 + 38 μm) were used during the flotation tests. The fundamental flotation model was used to back-calculate the induction times from the flotation experimental data. It was found that the induction times and the flotation rate constants could be used to quantify the flotation performances. However, for the same particle size fraction, the flotation recovery was very sensitive to the changes in the pulp chemical conditions while the flotation rates and particularly the induction times slightly changed. The attachment efficiency-induction time curve was significantly less sensitive to identify the changes in particle sizes than the flotation rate-induction time curves.